Bimbingan Emosional Mengembangkan Kemampuan Anak-Anak - farida, Farida (THUFULA, 2015)
Children phase has a variety of potential ability to be optimized in order to undergo all development tasks in line with the maximum growth, so ready to enter the next phase, namely: teenagers, adults, elderly. Cognitive potential to solve problems in life, emotional potential to adapt to the environment, and the children potential psychomotor is able to realize what he was thinking and feeling fit the norm for a man who is always active “go-no” to independence responsible. Therefore, education and counseling is done by adults (especially parents) for children to grow up to be independent human beings and with all his typical late can be tried in the hope that always “successful”. Modeling, habituation, giving guidance to understand the characteristic of the child will be more effective. The trick is to give “free” experience and play while learning among friends. The conditions for children have needs besides socializing with family get ready to enter formal educational institutions and non-formal, and various ways to respect the diversity of the environment. Hence the need for the feeling to feel fulfilled in the guidance of emotional given to children to be able to manage the basic emotions (happy, sad, disgusted, angry, disappointed, and surprised) that is held to be a human being adaptable, motivated and self-esteem and self-concept positive. Due to the positive expression of emotion to motivate children to develop cognitive abilities and psychomotor personal-social and spiritual.